The Influence of Career Development, Leadership, and Work Environment on Job Satisfaction - Destiya Nurmala Putri; Dina Novriyana (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to examine how career development, leadership, work environment affect job satisfaction and provide data-based recommendations to organisations regarding steps that can be taken to improve employee job satisfaction Design/methodology/approach – This study uses quantitative research methods, using primary data collected from a population of 59 employees working at St. Kristoforus Catholic School. Data analysis wan conducted using Partial Least Square (PLS) software with Moderated Regression Analysis. Findings – This study reveal that career development and work environment significantly increase job satisfaction. In contrast, leadership does not significantly increase job satisfaction. Research limitations/implications – This research is limited to a particular organization and this research can only be done in one sector so that the results cannot be directly applied to other sectors with different conditions.